Vaccines and Vaccination: Feature Papers - Pedro Plans-Rubió (Vaccines)
This Special Issue, entitled “Vaccines and vaccination: Feature Papers”, included articles that addressed various issues related to vaccines and vaccination, including studies assessing interventions to increase vaccination coverage [...]